2020
DOI: 10.3390/land9090294
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Ecosystem Services and Disservices in Valuing Smallholder Livestock and Poultry Production in Three Villages in South Africa

Abstract: This study presents an integrated examination of both the ecosystem services (ES) and ecosystem disservices (EDS) associated with smallholder animal husbandry in rural livelihoods in three villages in southeast South Africa. It recognises the contribution of ES supporting and resulting from smallholder livestock and poultry production, but also details the limiting factors or EDS, such as tick-borne disease, birds of prey or unpalatable rangeland, produced by the same system. Using a mixed-methods approach, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Other previous owners of cattle had sold them when the household needed cash (15%), suffered them being stolen (13%), or there was nobody to look after them (12%). The high proportion indicating that their animals had died indicates the precarious nature of animal husbandry in a region with frequent droughts and pervasive tick-borne diseases [38,39]. Thus, our broader-scale survey corroborates smaller empirical studies that have reported either respondents' sentiments of declines in cattle numbers and ownership [25,29] or actual declines based on counts of animals at different time points [24,40].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Other previous owners of cattle had sold them when the household needed cash (15%), suffered them being stolen (13%), or there was nobody to look after them (12%). The high proportion indicating that their animals had died indicates the precarious nature of animal husbandry in a region with frequent droughts and pervasive tick-borne diseases [38,39]. Thus, our broader-scale survey corroborates smaller empirical studies that have reported either respondents' sentiments of declines in cattle numbers and ownership [25,29] or actual declines based on counts of animals at different time points [24,40].…”
Section: Discussionsupporting
confidence: 74%
“…It is likely that some of these will work in tandem, such as wildfires and overgrazing being exacerbated by drought conditions. Respondents in the Herd-Hoare and Shackleton [39] study in the Eastern Cape also perceived a decline in the condition of their rangelands, which they attributed to the injudicious use of fire, which echoes the work of Kepe and Scoones [47] reporting how different fires regimes (and in combination with different grazing intensities) have altered the dominance of particular grass species, often in favour of less palatable ones. These changes have been ongoing for a lot longer than the 15-year window used in our study [47].…”
Section: Discussionmentioning
confidence: 83%
“…Ecosystem services are well-known and documented especially in a southern African context (van Jaarsveld et al, 2005;Egoh et al, 2008;Fenta et al, 2020;Mowat and Rhodes, 2020) and these are linked directly to human-environment (socio-ecological) relationships and aspects of sustainable development (Bailey and Buck, 2016;Sigwela et al, 2017;Cerretelli et al, 2018;Bengochea Paz et al, 2020). Many local case studies worldwide have described different ecosystem services and their uses by communities in different, mainly agricultural, contexts (e.g., Mensah et al, 2017;Swemmer et al, 2019;Herd-Hoare and Shackleton, 2020;Lhoest et al, 2020). The conceptual basis for understanding these ecosystem services is well-founded because it is based on ecological processes set in a landscape context, and studies of ecosystem services are framed by well-defined theoretical approaches, which include:…”
Section: Environmental Services As a Basis For Understanding Of Soil Food And Water Systems The Nature Of Ecological Environmental Servicmentioning
confidence: 99%
“…Meat and egg production are crucial for the nutrition of families in Africa (Alabi et al, 2012;Motsepe et al, 2016) and they are marketed as enhancing incomes (Nondzutha et al, 2020). Furthermore, indigenous chickens are used in communities for traditional events (Herd-Hoare and Shackleton, 2020).…”
Section: Introductionmentioning
confidence: 99%